A integração da indústria 4.0 na fabricação de termoplásticos: desafios, soluções e efeitos na otimização operacional - Barreto, Davi Araújo (Brasil, 2025)
This paper analyzes Industry 4.0, focusing on advanced technologies such as the Internet of Things (IoT) and Artificial Intelligence (AI). Things (IoT) and Artificial Intelligence (AI), analyzing their impacts on the production of production and related services. The research examines how these innovations are profoundly expanding production processes, increasing efficiency, flexibility and customization. It also looks at challenges such as the qualification of employees, organizational adaptation, cybersecurity and infrastructure. The method adopted includes a literature review and a case study. The results indicate significant barriers, but suggest innovative strategies to maximize benefits and increase competitiveness.